Synthesis, Characterization, Oxidative Dna Cleavage And Dna Binding Studies Of Mixed Ligands Copper(Ii) Complexes - Tan, Yi Han (2013)
Six ternary copper(II) complexes of amino acids and polypyridyl ligands with a general formula of [Cu(AA)(B) Cl]·nH2O or [Cu(AA)(B)(H2O)]Cl·nH2O, where AA = DL-threonine, DL-phenylalanine, and DL-valine; B = 2,2’-bipyridyl, 4,4’-dimethyl-2,2’-dipyridyl, and 1,10-phenanthroline are synthesized. The complexes are characterized by CHN elemental analysis, AAS, FT-IR, and UV-Vis and have been structurally characterized by X-ray crystallography. All the complexes formed slightly distorted square-pyramidal coordination geometries. The electronic absorption spectra of the complexes show very low intensity of d-d electronic band in the range of 600-635 nm in Tris-HCl/NaCl (5:5 mM) pH 7.2 buffer solution. The DNA binding interaction with CT-DNA has been investigated by electronic absorption spectral titration and viscosity measurements. The results revealed that the phenanthroline complexes interact with CT-DNA through intercalation while bipyridyl complexes bind to CT-DNA through groove binding mode. The calculated intrinsic binding constant (Kb) of all the complexes are in the range of 0.5-6.2 × 105 M-1. All the copper(II) complexes are found to promote efficient DNA cleavage activities at low concentration in the presence of H2O2. The studies show that [Cu(Phe)(Phen)Cl]·3H2O exhibits the highest DNA binding and nuclease activity among the six copper(II) complexes.